Lung carcinoma presenting as bilateral metastases in the mandibular gingivae: a case report and literature review. (2nd November 2021) - Elsherif, Nusaybah; Jeremic, Predrag; Blackburn, Tim
Abstract : This case report describes the rare presentation of lung carcinoma as bilateral masses affecting the mandibular gingivae. Although metastatic disease to the mouth is rare, accounting for only 1% of oral malignancies, it is essential to ensure that the presence of cancer is included in any differential diagnosis. CPD/Clinical Relevance: All oral abnormalities persisting for longer than 3 weeks should be referred urgently for specialist assessment and biopsy.